2016
DOI: 10.1177/0884533616680840
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding Set Handling Techniques

Abstract: All 3 EFS handling techniques displayed low bacterial growth. RTH was superior in bacterial growth, nursing time, and supply costs. Since not all pediatric formulas are available in RTH, we conclude that refrigerating the EFS between uses is the next most efficacious method for handling the EFS between bolus feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Other studies have demonstrated that bacteria enter the GI system through enteral feeding systems, especially when proper cleansing techniques are not followed. The greatest source of known enteral feeding system contamination has been poor hand hygiene by clinicians 8,41 . Osland et al recommended following the manufacturers' guidelines for the duration of equipment use, including cleansing and drying time 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have demonstrated that bacteria enter the GI system through enteral feeding systems, especially when proper cleansing techniques are not followed. The greatest source of known enteral feeding system contamination has been poor hand hygiene by clinicians 8,41 . Osland et al recommended following the manufacturers' guidelines for the duration of equipment use, including cleansing and drying time 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The greatest source of known enteral feeding system contamination has been poor hand hygiene by clinicians. 8,41 Osland et al recommended following the manufacturers' guidelines for the duration of equipment use, including cleansing and drying time. 14 Their systematic review found variability in reuse practices for enteral feeding equipment in the outpatient setting.…”
Section: Potential For Gi Tract Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a lack of robust evidence supporting water as a method of cleaning, it is recommended to rinse administration sets to help clear debris and to prevent mechanical obstructions. Lyman et al compared cleaning methods of pump feeding bags between uses, which tested (1) cleaning with sterile water, (2) refrigerating the bag between feedings, and (3) ready‐to‐hang (RTH) bags for bacterial growth 1 . RTH formula had the least bacterial growth; however, all three showed low bacterial growth overall.…”
Section: Section 1: Practice Recommendations For General Use Of Btfmentioning
confidence: 99%